2016
DOI: 10.1111/1467-9566.12402
|View full text |Cite
|
Sign up to set email alerts
|

‘Coz football is what we all have’: masculinities, practice, performance and effervescence in a gender‐sensitised weight‐loss and healthy living programme for men

Abstract: In this paper we use a social practice approach to explore men's experience of Football Fans in Training (FFIT), a group‐based weight management programme for men that harnesses men's symbolic attachment to professional football clubs to engage them in lifestyle change. FFIT is delivered by community coaches in clubs’ stadia and is gender‐sensitised in relation to context, content and style of delivery. Using a ‘toolkit’ of concepts from the work of Bourdieu, Goffman and Durkheim we analysed data from 13 focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 49 publications
6
65
0
2
Order By: Relevance
“…Participation in sports clubs has been shown to enable men to exchange life experiences with others who share similar interests and characteristics (Bunn et al, 2016), which could plausibly reduce feelings of loneliness and be related to fewer depressive symptoms, via the benefits of physical activity. The weaker association between participation in political and community organisations and loneliness is consistent with a recent study that found involvement in these activities was associated with an increase in depressive symptoms four years later, which the authors suggested may be due to the high effort and low reward incurred (Croezen et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Participation in sports clubs has been shown to enable men to exchange life experiences with others who share similar interests and characteristics (Bunn et al, 2016), which could plausibly reduce feelings of loneliness and be related to fewer depressive symptoms, via the benefits of physical activity. The weaker association between participation in political and community organisations and loneliness is consistent with a recent study that found involvement in these activities was associated with an increase in depressive symptoms four years later, which the authors suggested may be due to the high effort and low reward incurred (Croezen et al, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…, Guell et al ) there is growing interest in the notion of ‘health practices’ as a critical conceptual alternative to the individualising notion of ‘health behaviours’. This shift speaks to the growing body of critical social science research that calls for interventions that do not predominantly frame change in terms of individual responsibility for health (Bunn et al ). It also addresses concerns that behaviouralist and population focused research has ignored the significance of the social practice contexts of embodied activity or (im)mobility (Nettleton and Green ).…”
Section: Situating Parkrun As a ‘Health Practice’mentioning
confidence: 99%
“…Changing the target group to include boys or girls without internalizing problems in order to recruit more adolescents to the groups may decrease the effectiveness of the intervention for the girls who need it most. The importance of a shared habitus and experiences in public health interventions has been emphasized in other intervention groups (Bunn, Wyke, Gray, Maclean, & Hunt, 2016; Coalter, 2013) and may be equally important for adolescent girls with internalizing behaviour. However, more research is needed to find out whether mixed groups can be as effective.…”
Section: Discussionmentioning
confidence: 99%